Crucial considerations: Sex differences in the epidemiology, diagnosis, treatment, and outcomes of acute pulmonary embolism in non‐pregnant adult patients - Angela F. Jarman; Bryn E. Mumma; Kajol S. Singh; Craig D. Nowadly; Brandon C. Maughan (Journal of the American College of Emergency Physicians Open)
Abstract Acute pulmonary embolism (PE) affects over 600,000 Americans per year and is a common diagnostic consideration among emergency department patients. Although there are well‐documented differences in the diagnosis, treatment, and outcomes of cardiovascular conditions, such as ischemic heart disease and stroke, the influence of sex and gender on PE remains poorly understood. The overall age‐adjusted incidence of PE is similar in women and men, but women have higher relative rates of PE during early and mid‐adulthood (ages 20–40 years); whereas, men have higher rates of PE after age 60 years. Women are tested for PE at far higher rates than men, yet women who undergo computed tomography pulmonary angiography are ultimately diagnosed with PE 35%–55% less often than men. Among those diagnosed with PE, women are more likely to have severe clinical features, such as hypotension and signs of right ventricular dysfunction. When controlled for PE severity, women are less likely to receive reperfusion therapies, such as thrombolysis. Finally, women have more bleeding complications for all types of anticoagulation. Further investigation of possible sex‐specific diagnostic and treatment algorithms is necessary in order to more accurately detect and treat acute PE in non‐pregnant adults.